Use of high-thermal conductive aluminum nitride based ceramics in vacuum UHF electronic devices - Chasnyk, V. I. (Technology and design in electronic equipment, 2013)
Analysis of properties and characteristics of the alumina, beryllium oxide and aluminium nitride based ceramic materials used in UHF electronic devices has been made. It was shown that the complex of parameters including structural and functional characteristics of the high-thermal conductive aluminium nitride ceramics prevail over all types of alumina ceramics and is not lower than the same characteristics of the beryllium oxide ceramics especially at the temperatures higher than 450 °C. The examples of the prevailing use of the aluminium nitride ceramics inside vacuum UHF-region devices: TWT’s and klystrons.